Landscapes of membrane protein interactions from high-throughput MD simulations using the daft approach - Wassenaar, Tsjerk A.; Pluhackova, Kristyna; Moussatova, Anastassiia; Sengupta, Durba; Marrink, Siewert-Jan; Tieleman, D. Peter; Boeckmann, Rainer A. (Biophysical Journal, 2015)

Lipid-dependent conformational landscape of the ErbB2 growth factor receptor dimers - Gopal, Srinivasa M.; Pawar, Aiswarya B.; Wassenaar, Tsjerk A.; Sengupta, Durba (Chemistry and Physics of Lipids, 2020)
Altered lipid metabolism has been linked to cancer development and progression. Several roles have been attributed to the increased saturation and length of lipid acyl tails observed in tumors, but its effect on signaling receptors is still emerging. In this work, we have analyzed the lipid dependence of the ErbB2 growth factor receptor dimerization that plays an important role in the pathogenesis of breast cancer. We have performed coarse-grain ensemble molecular dynamics simulations to comprehensively sample the ErbB2 monomer-dimer association. Our results indicate a dynamic dimer state with a complex conformational landscape that is modulated with increasing lipid tail length. We resolve the native N-terminal ``active'' and C-terminal ``inactive'' conformations in all membrane compositions. However, the relative population of the N-terminal and C-terminal conformers is dependent on length of the saturated lipid tails. In short-tail membranes, additional non-specific dimers are observed which are reduced or absent in long-tailed bilayers. Our results indicate that the relative population as well as the structure of the dimer state is modulated by membrane composition. We have correlated these differences to local perturbations of the membrane around the receptor. Our work is an important step in characterizing ErbB dimers in healthy and diseased states and emphasize the importance of sampling lipid dynamics in understanding receptor association.
Keywords: ErbB2 dimer; Lipid effects; Martini coarse-grained simulations; Membrane protein structure; Transmembrane association